Comparative Study of UCC and UEW B.Ed JHS Visual Art Options as Initial Teacher Preparation for the New Creative Arts and Design Curriculum for JHS - Alhassan, Hamza; Al-Hassan, Bawa; Osei, Mavis (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: The purpose of this study, therefore, is to compare the developed JHS visual art curricula of the two universities (UCC and UEW) as being implemented in the colleges of education, vis-a-vis the new JHS Creative Arts and Design curriculum to find out which of the curricula covers all aspects of Creative Arts and Design in JHS. Methodology: The study adopted a qualitative research approach using document analysis and autoethnography as data collection instruments. Main Findings: The study found that whereas UCC offers a combined major of visual art, UEW offers visual art as a standalone programme but both models of visual art education do not meet the full complement of the Creative Arts and Design subject in the JHS because the performing art aspect is not catered for in both models. Novelty/Originality of this study: The study recommends that both curricula should be reviewed to factor in the performing art aspect of the JHS Creative Arts and Design subject to enable them to train teachers who are fit for purpose.